Impact of the chemical precursor on the crystalline constitution of nano-CuO/TiO2 films. (October 2015) - Forcade, F.; Snyders, R.; Guisbiers, G.; Gonzalez, B.; Noirfalise, X.; Vigil, E.
Abstract: More and more interest is dedicated to nano-CuO/TiO2 mesoporous films which could be used in solar energy converting structures, sensors and photocatalysis applications. In this work we have studied the synthesis of CuO/TiO2 nanocomposite films using a low temperature modified wet-impregnation technique. Copper(II) formate and copper(II) acetate aqueous solutions with varying concentrations are used as precursors for deposition of cupric oxide inside mesoporous TiO2 layers. The obtained nanocomposite is characterized using XRD, SEM, AFM and UV–vis spectroscopy. Results show that the optical absorption spectrum of TiO2 is extended significantly in the visible region and a CuO energy gap E g  = 1.4 eV is deduced from the absorption edge. XRD experiments show evidence of CuO nanocrystals when using cupric formate aqueous solution as a precursor while for cupric acetate-prepared compound, no XRD peaks are observed suggesting a disordered CuO phase in that case.